2016
DOI: 10.1155/2016/5126069
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Drivers and Outputs for Software Firms: Literature Review and Concept Development

Abstract: Software innovation, the ability to produce novel and useful software systems, is an important capability for software development organizations and information system developers alike. However, the software development literature has traditionally focused on automation and efficiency while the innovation literature has given relatively little consideration to the software development context. As a result, there is a gap in our understanding of how software product and process innovation can be managed. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 117 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…Over 20 years later, Rose and Furneaux (2016) surveyed ninety three papers and showed that new software functionality was identified as the most common factor for software innovation. Mohanani et al (2017) also carried out an extensive literature review on, among other aspects, how creativity is measured in software engineering.…”
Section: Factors Impacting the Novelty Of Software Productsmentioning
confidence: 99%
“…Over 20 years later, Rose and Furneaux (2016) surveyed ninety three papers and showed that new software functionality was identified as the most common factor for software innovation. Mohanani et al (2017) also carried out an extensive literature review on, among other aspects, how creativity is measured in software engineering.…”
Section: Factors Impacting the Novelty Of Software Productsmentioning
confidence: 99%
“…ICT services provide stable revenue while the development of new products can provide substantial profit margins (Bonaccorsi et al 2006;Tanriverdi and Lee 2008;Sanio and Marjakoski 2009;Suarez et al 2013). Other studies frame success as the ability of ICT firms to develop robust technical, managerial, and marketing and client relations capabilities (Banerjee, 2003;Athreye, 2005;Ethiraj et al, 2005;Chaminade and Vang, 2008b;Li et al, 2010;Lema, 2014;Rose and Furneaux, 2016). Athreye (2005), for example, shows that the success of Indian outsourcing firms hinged on the development of managerial capabilities that enable large software development teams to deliver quality ICT services to firms located anywhere in the world.…”
Section: Technology Upgrading: Firm-level Capability Developmentmentioning
confidence: 99%
“…In our current society, the capacity of performing tasks with higher efficiency and precision is increasingly sought by automation [7]. In this way, the productive systems must ensure competency, considering a market that is increasingly more demanding and competitive [8].…”
Section: Introductionmentioning
confidence: 99%